2017
DOI: 10.1002/ajmg.a.38161
|View full text |Cite
|
Sign up to set email alerts
|

Cornelia de Lange syndrome and molecular implications of the cohesin complex: Abstracts from the 7th biennial scientific and educational symposium 2016

Abstract: Cornelia de Lange Syndrome (CdLS) is due to mutations in the genes for the structural and regulatory proteins that make up the cohesin complex, and is considered a cohesinopathy disorder or, more recently, a transcriptomopathy. New phenotypes have been recognized in this expanding field. There are multiple clinical issues facing individuals with all forms of CdLS, particularly in the neurodevelopmental system, but also gastrointestinal, cardiac, and musculoskeletal. Aspects of developmental and cell biology ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Whether the AD pathology is caused by cohesinopathy, centrosome defect, or the common consequence that is prolonged mitosis must be distinguished. Cohesinopathy in humans leads to diseases with cancer proneness, developmental malformation, and/or intellectual disability and behavioral issues, such as Cornelia de Lange syndrome or mutations in STAG1 or STAG2 (Kline et al., 2017; Kumar et al., 2015). The symptoms suggest that maintenance of chromosome cohesion may play a role more critical than previously anticipated in brain functions.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the AD pathology is caused by cohesinopathy, centrosome defect, or the common consequence that is prolonged mitosis must be distinguished. Cohesinopathy in humans leads to diseases with cancer proneness, developmental malformation, and/or intellectual disability and behavioral issues, such as Cornelia de Lange syndrome or mutations in STAG1 or STAG2 (Kline et al., 2017; Kumar et al., 2015). The symptoms suggest that maintenance of chromosome cohesion may play a role more critical than previously anticipated in brain functions.…”
Section: Discussionmentioning
confidence: 99%
“…Although SgoL1 mutation itself remains under-characterized in the human LOAD brain, many other causes, e.g. spindle checkpoint-activating events, such as the aneuploidy that is prevalent in aged brains [115] or dysfunction in mitosis-regulatory genes that also induce cohesinopathy (genes of cohesins or centrosome components), can produce prolonged mitosis in the human brain that results in the functional equivalent of Sgo1 mutation [74,[116][117][118][119] Implications of LOAD mouse model on AD drug research and development (R&D)…”
Section: Late-onset Accumulation Of Amyloid-beta In Sgo1 Brainmentioning
confidence: 99%
“…Furthermore, short stature occurs proportionally and hypertrichosis is commonly observed. 3,4 Previous studies have shown that upper extremity defects ranging from clinodactyly to severe reduction defects of the forearms have been reported in approximately 30% of individuals with CdLS. Although, cardiac anomaly is not a major criterion of the disease, approximately 50% of CdLS patients presented with congenital heart defects.…”
Section: Introductionmentioning
confidence: 99%
“…Although, cardiac anomaly is not a major criterion of the disease, approximately 50% of CdLS patients presented with congenital heart defects. 4 5 Approximately 50% of individuals with CdLS have ocular anomalies with the most common being ptosis, myopia, nystagmus, and strabismus. Many individuals with CdLS demonstrate neuropsychiatric features including seizures, autistic behavior, and self-destructive tendencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation